The Norm of Marriage Age Limit and Cultural Contestation of Child Marriage Law in Rural Communities - Syahrudin Hidayat; Abdul Ghofur; Ummul Baroroh (Jurnal Hukum Islam, 2023)
Changes in state legal norms regarding the age limit for marriage have been implemented to reduce the number of child marriages in Indonesia. However, child marriage is still practised, especially in rural areas of Central Java. This paper discusses three main problems, namely the prevalence of child marriage in rural areas, the dominance of tradition and dogmatic understanding of religion, the impact of poverty and social media technology as factors influencing child marriage in rural communities, and the transformation of social engineering through education and economic improvement to overcome the problem. child marriage in rural areas. This legal sociology research uses a qualitative approach.  Data analysis techniques use interactive models. The study shows that the prevalence of child marriage increased by 300% after changes in norms regarding the age limit for marriage, especially in rural communities. This happens because child marriage in rural communities is a tradition passed down through generations. Traditions and religious norms understood by rural communities as allowing child marriage have become an unwritten legal system implemented by the community. Changes in state legal norms regarding marriage age limits have the potential to disrupt established social institutions, so that sociologically they are not binding as norms for rural communities, giving rise to an apathetic public response. Therefore, efforts to improve the education and economic systems with a holistic approach are very effective in overcoming the problem of child marriage in rural communities.